PENGUATAN EKONOMI POLITIK MASYARAKAT SEKITAR MA’HAD AL-ZAYTUN MELALUI PENYULUHAN EKONOMI KREATIF DI DESA SANCA, GANTAR, INDRAMAYU - Rahim, Abdur; Baldannudin, Muhammad Idrus; Salsabila, Fatikha; Fuadzi, Farid Anwar; Awaluddin, Bagus Tegar; Maulia, Shepti; Nurfaiza, Atika; Ramadhan, Farhan Arif (Jurnal Abdimas Bina Bangsa, 2024)
Creative economy counseling in Sanca Village, Gombangan Block, was held as an initial step to strengthen the political economy. Creative economy counseling discusses the strategy of the community's role in optimizing the utilization of local assets in the form of secang trees (Caesalpinnia sappan) which can be a creative economic business opportunity. Community cooperation in managing their natural resources can lead to the goal of strengthening the political economy. In order to follow up, extension activities related to the partnership-based creative economy were held, which were carried out by socializing the processing of sappan trees into herbal drink products, along with appealing to the community to succeed in the social assistance program, namely holding a bazaar of used clothes worth wearing to be distributed free of charge as a form of social care for the community. The purpose of the socialization was intended to make the community willing to become business partners, namely the community was invited to become a distributor of raw materials in the form of sappan wood as well as a retailer of finished materials in the form of ready-to-use trademarked beverage products. The method of implementing activities is door to door, meaning that the extension workers who have been determined per group, educate and socialize product knowledge to the community they meet directly by visiting houses in the Gombangan Block area. Based on the results of the extension activities, factors that caused the partnership program to be considered promising and appropriate were found, among others: First, the community's experience in participating in training to process sappan wood into valuable beverage products. Second, the community is accustomed to planting sappan trees for fencing purposes. Third, the community's fighting spirit to improve their standard of living. However, the community has not shown interest in accepting the offer to become a business partner due to the community's busy schedule as farmers and lack of time management skills